L'influence interpersonnelle et les gains thérapeutiques escomptés en counselling - Prince-Mador, Monique; Perron, Jacques; Charbonneau, Claude (Canadian Journal of Counselling and Psychotherapy, 2011)
Using a social psychological paradigm in which counselling is defined as an interpersonal influence process, this article examines the relationships between a therapist's perceived expertness, attractiveness, and trustworthiness, on the one hand, and expected therapeutic gains for others and for oneself, on the other hand. Results collected from 126 subjects show that perceived expertness and, to a lesser degree, trustworthiness, are closely related to expected therapeutic gains for others whereas only perceived expertness is associated with expected therapeutic gains for oneself.